Nutrient solution strength affects growth, physiology, biochemistry and fruit quality of Korean strawberry ‘Kuemsil’ in a recycling hydroponic system - Zebro, Mewuleddeg; Baek, Jeong-Hyeon; Kim, Minkyung; Jeong, Youngae; Rabbani, M. G.; Choi, Ki-Young (Frontiers in Plant Science, 2025)
IntroductionDetermining the optimal nutrient solution strength is critical for sustainable strawberry production in hydroponics. This study investigated the effects of nutrient solution strength on growth, physiological performance, antioxidant activity, and fruit quality of the strawberry cultivar ‘Kuemsil’ grown in a recycling hydroponic system.MethodsFour nutrient solution strengths were tested: one-third (1/3S), half (1/2S), two-thirds (2/3S), and full strength (1S) of the Japan Horticultural Research Institute solution, using coconut coir substrate in a greenhouse for 175 days from September 2024 to May 2025. Plant growth traits, photosynthetic parameters, pigment concentrations, antioxidant activity, and fruit quality attributes were measured.ResultsResults showed that the 2/3S treatment significantly enhanced vegetative growth, photosynthetic rate, stomatal conductance, and pigment content. Furthermore, the 2/3S treatment improved antioxidant capacity, including total phenolic content, total flavonoid content, DPPH radical scavenging activity, and ferric reducing antioxidant power. Moreover, antioxidant enzyme activities, such as peroxidase and catalase, were substantially higher under the 2/3S treatment compared to the other treatments. Fruit weight, firmness, soluble solids content, and mineral contents (potassium, magnesium, phosphorus) were also highest under 2/3S, whereas 1/3S consistently produced the lowest values. In contrast, the 1/3S treatment resulted in higher values for absorbed energy per reaction center (ABS/RC) and trapped energy per reaction center (TRo/RC). These increases suggest that the reaction centers were subject to greater excitation pressure and retained more of the absorbed energy under reduced nutrient strength.DiscussionBased on these findings, the 2/3S treatment provided the best overall balance of growth, physiological performance, and fruit quality. Therefore, applying a two-thirds-strength nutrient solution is optimal for improving both productivity and fruit quality of the ‘Kuemsil’ strawberry cultivar under recycling hydroponic conditions.